Do environmental education fieldtrips strengthen children's connection to nature and promote environmental behaviour or wellbeing? - Julie Whitburn; Wokje Abrahamse; Wayne Linklater (Current Research in Ecological and Social Psychology, 2023)
Nature-based environmental education could be an effective way to promote children's connection to nature, every-day pro-environmental behaviour (PEB) and psychological wellbeing. We conducted a longitudinal, quasi-experimental field study with children aged 7 - 13 years from schools who attended environmental education fieldtrips in Wellington, New Zealand (N = 257). Data was collected via a self-administered questionnaire and a gifting (Token) experiment immediately before and four weeks after children attended an environmental education fieldtrip. Results indicate that environmental education was associated with a small increase in children's PEB and an increase in support for conservation relative to a control group. However, the intervention had little effect on children's connection to nature, vitality or life satisfaction. The effect of the intervention on connection to nature was moderated by children's pre-existing levels of connection to nature. Fieldtrips only increased connection to nature for those children who had higher levels of connection to nature before the intervention.Reconnecting people to nature is considered a deep leverage point to promote individual PEB and co-benefits such as individual wellbeing. Our results provide modest and nuanced support for its influence on PEB but not wellbeing.